The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1515/cclm-2020-0026
|View full text |Cite
|
Sign up to set email alerts
|

Availability and analytical quality of hemoglobin A1c point-of-care testing in general practitioners’ offices are associated with better glycemic control in type 2 diabetes

Abstract: AbstractBackgroundIt is not clear if point-of-care (POC) testing for hemoglobin A1c (HbA1c) is associated with glycemic control in type 2 diabetes.MethodsIn this cross-sectional study, we linked general practitioner (GP) data on 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 19 publications
(33 reference statements)
0
9
0
Order By: Relevance
“… 15 Another ROSA4 study indicated that point-of-care HbA 1c testing in general practice was linked to better glycaemic regulation in patients with T2D. 20 Finally, ROSA4 has reported that GP adherence to recommended standard follow-up procedures in T2D was related to both clinic structure and workload. 21 …”
Section: Findings To Datementioning
confidence: 99%
“… 15 Another ROSA4 study indicated that point-of-care HbA 1c testing in general practice was linked to better glycaemic regulation in patients with T2D. 20 Finally, ROSA4 has reported that GP adherence to recommended standard follow-up procedures in T2D was related to both clinic structure and workload. 21 …”
Section: Findings To Datementioning
confidence: 99%
“…Operational and economic outcomes can also be taken into account when setting APS, provided that patient health outcomes are not unduly compromised. For example, HbA1c measured using a point of care device with low bias in the clinic facilitates faster decisions on the adjustment of treatment, which can be better communicated to patients at their clinic visit and thus leads to increased adherence with treatment [7]. This raises the important concept of balancing priorities for both health outcomes and costs.…”
Section: Evidence-based Analytical Performance Specificationsmentioning
confidence: 99%
“…The provision of a glycated haemoglobin (HbA1c) result by PoCT at the time of consultation leads to improvement in glycaemic control. 3 In addition, GPs have long argued that PoCT also brings other benefits to their everyday practice.…”
Section: Point-of-care Testing-has It Come Of Age?mentioning
confidence: 99%